IMPLEMENTATION OF THE BUSINESS MODEL CANVAS ON MOM N GO COOKIES - Rayhan Praditya Oktavianto; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2026)
Abstract: This research focuses on the application of Business Model Canvas to Mom N Go Cookies, a small and medium enterprise (SME) engaged in food production, especially cookies. This research aims to analyze the business model design of Mom N Go Cookies in accordance with current conditions, as well as provide recommendations for effective and efficient business development strategies. The method used in this research is a qualitative approach through in-depth interviews, observations, and literature studies. Business Model Canvas was chosen because of its ability to provide a clear and structured visualization of the essential elements of a business, such as customer segments, value propositions, key resources, and revenue streams. The results showed that Mom N Go Cookies has great potential to grow through product innovation, customer segment expansion, and optimization of marketing strategies, both online and offline. Business strategy development recommendations include product diversification and increased collaboration with strategic partners. This research is expected to provide insight for SME entrepreneurs in planning Business Model Canvas-based business strategies and help Mom N Go Cookies compete in an increasingly competitive market.Abstraksi: Penelitian ini berfokus pada penerapan Business Model Canvas pada Mom N Go Cookies, sebuah usaha kecil menengah (UMKM) yang bergerak di bidang produksi makanan, khususnya kue kering. Penelitian ini bertujuan untuk menganalisis desain model bisnis Mom N Go Cookies sesuai dengan kondisi saat ini, serta memberikan rekomendasi strategi pengembangan bisnis yang efektif dan efisien. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif melalui wawancara mendalam, observasi, dan studi pustaka. Business Model Canvas dipilih karena kemampuannya memberikan visualisasi yang jelas dan terstruktur mengenai elemen-elemen penting dari bisnis, seperti segmen pelanggan, proposisi nilai, sumber daya utama, dan aliran pendapatan. Hasil penelitian menunjukkan bahwa Mom N Go Cookies memiliki potensi besar untuk berkembang melalui inovasi produk, perluasan segmen pelanggan, serta optimalisasi strategi pemasaran, baik secara online maupun offline. Rekomendasi pengembangan strategi bisnis meliputi diversifikasi produk dan peningkatan kolaborasi dengan mitra strategis. Penelitian ini diharapkan dapat memberikan wawasan bagi pengusaha UMKM dalam merencanakan strategi bisnis berbasis Business Model Canvas dan membantu Mom N Go Cookies bersaing di pasar yang semakin kompetitif.